2020
DOI: 10.1155/2020/3093874
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Study of the Distal Biceps Femoris Muscle in relation to the Normal and Variant Course of the Common Peroneal Nerve: A Possible Cause of Common Peroneal Entrapment Neuropathy

Abstract: The most frequent mononeuropathy in the lower extremity has been reported as the common peroneal nerve entrapment neuropathy (CPNe) around the head and neck of the fibula, although the mechanism of the neuropathy in this area cannot be fully explained. Therefore, the aim of this cadaveric study was to evaluate the relationship between morphologic variations of the distal biceps femoris muscle (BFM) and the course of the common peroneal nerve (CPN) and to investigate the incidence and morphological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…By constructing a 3D model of the biceps femoris tendon at various knee flexion angles, we were able to observe that the position of the CPN remained relatively fixed as it descended along the biceps femoris and its tendon. Park et al 22 suggested that a tunnel is formed between the biceps femoris muscle and the lateral gastrocnemius muscle, which keeps the CPN relatively fixed at that location and lacks cushioning tissue, making the CPN more susceptible to injury. We also found from the 3D model that as the knee flexes, the biceps femoris muscle moves posteromedially along the longitudinal axis of the femoral shaft, utilizing the fibular head as a pivot point.…”
Section: Discussionmentioning
confidence: 99%
“…By constructing a 3D model of the biceps femoris tendon at various knee flexion angles, we were able to observe that the position of the CPN remained relatively fixed as it descended along the biceps femoris and its tendon. Park et al 22 suggested that a tunnel is formed between the biceps femoris muscle and the lateral gastrocnemius muscle, which keeps the CPN relatively fixed at that location and lacks cushioning tissue, making the CPN more susceptible to injury. We also found from the 3D model that as the knee flexes, the biceps femoris muscle moves posteromedially along the longitudinal axis of the femoral shaft, utilizing the fibular head as a pivot point.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the patient who had fracture of fibular head combined with injury of common peroneal nerve only received X-ray examination when consulted at the emergency department and the doctor in the emergency department did not follow the standard of visual examination, touch, movement and measurement for orthopedics during physical examination, and failed to find timely signs of tenderness of the lateral side of the left knee and numbness of the lateral part of the left lower leg and failed to instruct the patient to follow up regularly and have MRI examination, which resulted in missed diagnosis. Some scholars have proved that 5 if the compression or injury of common peroneal nerve is not found in time, there is the possibility of nerve inactivation, which may cause decreased sensation and pain of the innervated area, 6 and even irreversible damage to the movement. It can be recovered effectively by timely detection and early surgery release.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the proximal division of the femoral cutaneous nerve could generate compression under the inguinal ligament. Seven studies [52][53][54][55][56][57]60,63] analyzed the compression of the FN, which was compressed in the following regions: entrapment by the accessory belly of the iliacus muscle occurs where the NF divides into two branches, one that goes over the accessory iliacus muscle and another that passes between the iliacus muscle and the accessory belly, the latter being where the nerve will have possible compression; another variation that can generate compression of the NF is where the iliacus muscle covers the NF, or where the nerve pierces the iliacus muscle; and finally, there is a critical fibromuscular ring between the inguinal ligament and the lateral part of the iliopsoas muscle, but some accessory bellies of the greater psoas muscle can compress the FN. For the compression of the ON, four studies were included [65][66][67][68], one in which compression was produced by a surgical complication due to vaginal tape for the treatment of urinary incontinence, which intra-surgically produced an iatrogenic compression of the ON, leaving the patient with symptoms in the nerve innervation territory.…”
Section: Thigh Region Variantsmentioning
confidence: 99%